2023
DOI: 10.1111/joim.13607
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral lymphocyte count defines the clinical phenotypes and prognosis in patients with anti‐MDA5‐positive dermatomyositis

Abstract: Z, et al. Peripheral lymphocyte count defines the clinical phenotypes and prognosis in patients with anti-MDA5-positive dermatomyositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a large Chinese cohort study of patients with MDA5-DM, patients were classi ed into three subgroups according to peripheral lymphocyte count. The results proved severe lymphopenia is strongly associated with high mortality, and a normal peripheral lymphocyte number at baseline predicts a better prognosis [4] . However, a single indicator fails to accurately predict a particular outcome, a prediction model incorporating several relevant risk factors may enhance predictive power.…”
Section: Completely Learning Of Clinical Conditions Is Helpful For Pr...mentioning
confidence: 90%
“…In a large Chinese cohort study of patients with MDA5-DM, patients were classi ed into three subgroups according to peripheral lymphocyte count. The results proved severe lymphopenia is strongly associated with high mortality, and a normal peripheral lymphocyte number at baseline predicts a better prognosis [4] . However, a single indicator fails to accurately predict a particular outcome, a prediction model incorporating several relevant risk factors may enhance predictive power.…”
Section: Completely Learning Of Clinical Conditions Is Helpful For Pr...mentioning
confidence: 90%
“…Anti-MDA5 antibody-positive dermatomyositis (MDA5 + DM), a distinct subtype of idiopathic inflammatory myopathies (IIM), is significantly associated with interstitial lung disease (ILD), particularly the rapidly progressive interstitial lung disease (RP-ILD). MDA5 + DM with RP-ILD is often resistant to traditional treatment, and despite aggressive interventions, the mortality rate is still as high as 50-70% [ 1 , 2 ]. Hence, early identification of high-risk RP-ILD patients is a vital aspect of improving prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…MDA5 + DM is a heterogeneous disease, with substantial variability in clinical presentation, treatment response, and patient outcomes. About 30 ~ 50% of patients exhibited the life-threatening RP-ILD [ 1 , 3 ], conversely, while about 60% of patients MDA5 + DM displayed mild symptoms with good prognosis. Therefore, accurate prediction of patients at high risk of RP-ILD may aid in decision-making on therapeutic strategies and assist in preventing overtreatment of “low-risk” patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than describing phenotypes, clusters and decision trees provide better guidance for clinical practice if they follow commonly accepted definitions of MDA5-DM and RP-ILD, use a few easily and objectively measured clinical characteristics known at the time of diagnosis, predict a patient’s prognosis reliably and are validated by replication. As a striking illustration of this viewpoint, one of the four studies demonstrated that phenotypic clusters performed equally well if they were based on lymphocyte count only instead of a multitude of characteristics [ 5 ]. Another study, not included in the review, showed similar accuracy of phenotypic clusters based on immune cell phenotypes [ 7 ].…”
mentioning
confidence: 99%